Viewpoint: A Contributory Role of Shell Ginger (Alpinia zerumbet) for Human Longevity in Okinawa, Japan? - Teschke, Rolf; Xuan, Tran Dang (Nutrients, 2018)
The longevity of the population in the Okinawa Islands of Japan has been ascribed to genetic factors and the traditional Okinawa cuisine, which is low in calories and high in plant content. This diet includes shell ginger (Alpinia zerumbet (Pers.) B.L. Burtt & R.M. Sm) of the ginger family (Zingiberaceae). Due to its local popularity, Alpinia zerumbet has become the subject of a good deal of study at the University of the Ryukyus in Okinawa. Personal local experience and review of the literature now suggest that culinary shell ginger may contribute to longevity among the population in Okinawa. This is supported by its abundant phytochemical content, with antioxidant and anti-obesity properties. The major bioactive phytochemicals are dihydro-5,6-dehydrokawain (DDK; 80–410 mg g−1 fresh weight), 5,6-dehydrokawain (DK; ≤100 mg g−1), and essential oils, phenols, phenolic acids, and fatty acids (≤150 mg g−1 each). Further, Alpinia zerumbet extends the lifespan in animals by 22.6%. In conclusion, culinary shell ginger may significantly contribute to human longevity in Okinawa.